Assessing the Impact of Prophylactic Vaccines on HPV Prevalence - Azevedo, F.; Esteva, L.; Ferreira, C.p. [UNESP] (Sociedade Brasileira de Matemática Aplicada e Computacional, 2019)
A mathematical model considering female and male individuals is proposed to evaluate vaccination strategies applied to control of HPV transmission in human population. The basic reproductive number of the disease, R 0 is given by the geometric mean of the basic reproductive number of female and male populations. The model has a globally asymptotically stable disease-free equilibrium whenever R0<1. Furthermore, it has an unique endemic state when R 0 exceeds unity which is globally asymptotically stable. Numerical simulations were done to compare several different vaccination schedules. The results showed that the vaccination strategies that do not include vaccination of men can only control the disease if more than 90% of women are vaccinated. The sensitivity analysis indicated that the relevant parameters to control HPV transmission, in order of importance, are vaccine efficacy times the fraction of population that is vaccinated, disease recovery-rate, and disease transmission rate. Therefore, health politics that promoting the increase of vaccine coverage, and screening for the disease in both population can improve disease control.

Um modelo matemático á proposto para avaliar as estratégias de controle da transmissão do HPV na população humana (homens e mulheres). O número reprodutivo básico da doença, R 0, é dado pela média geométrica do número reprodutivo básico obtido nas populações femininas e masculinas. O modelo tem um equilíbrio livre da doença globalmente assintoticamente estável sempre que R0<1. Além disso, tem um estado endêmico único quando R0>1 que é globalmente assintoticamente estável. Simulações numéricas foram feitas para comparar vários esquemas de vacinação diferentes. Os resultados mostraram que as estratégias de vacinação que não incluem a vacinação de homens controlam a transmissão da doença se mais de 90 % das mulheres forem vacinadas. A análise de sensibilidade indicou que os parâmetros relevantes para controlar a transmissão do HPV, por ordem de importância, são a eficácia da vacina vezes a fração da população vacinada, a taxa de recuperação da doença e a taxa de transmissão da doença. Portanto, políticas de saúde que promovam o aumento da cobertura vacinal e a detecção da doença em ambas as populações podem melhorar o controle da doença.
Keywords: sensitivity analysis; basic reproductive number; ordinary differential equation; análise de sensibilidade; número reprodutivo básico; equações diferencias ordinárias